Charakterystyka gry w pilke reczna na podstawie najnowszych badañ - Czerwinski, J. (Human Movement, 2001)
Contemporary research on training process' efficiency includes two directions: 1) the analysis of links existing between selected motor, somatic, physiologic, psychological etc. abilities and the level of special (technical) ability and general tendencies of these abilities' changes as a result of systematic training; 2) optimisation of training process. Collected data is a starting point for formulating "master model" in handball, and also for undertaking operational research aimed at training process optimisation. In handball we have to find some reference points and define concrete aims which are to be gained during training process. Thus a coach should know precisely the demands players have to handle during a game. Knowing the game from the side of external demands, that is motoric activities and their intensity and internal demands concerning energetic sources should make a reference point for planning training intensity. With satisfaction it can be stressed that there occurred positive changes in sports fight in handball noticed on the basis of the latest European championship held in Croatia in 2000. The analysis concerns six leading European teams. A visible progress in the way of attacking and more passes dangerous for rivals were noticed, which indicates dynamic play in offence. Increased efficiency and group solutions in offence were perceived. Passive zone defence 6:0 disappears, and the tendency to active, aggressive, outpost defence prevails. Play in position offence is based on individual and group solutions. Solutions in position attack are conditioned by the level of technical preparation which is continuously improving. Positive changes in game character were observed, which indicates first of all a proper coaches' work who perceive the relation between handball popularity and its dynamics and number of risky - spectacular - solutions. The results of latest men European championships and other international meetings' research simultaneously indicate the necessity to improve training process in which motorics and techniques decide about the success in a game. Perfect mastering the required techniques enables doing the job with less energy input, and also it allows gaining better results. Correct technique mastering should be formed at the early age, paying special attention to learning technique-tactic solutions in 1 × 1 situations, and at the highly-classified players this ability should be further developed. Research concerning match activities of handball players against actively organised defence shows that the main structural elements of offence are offence phases which, taking into consideration the character and preferences of the offenders' co-operation, can be divided into three groups: - passive attack phase, - active attack phase, - final phase. On the basis of the result analysis three quantities of the pace of mutual offending activities were defined, according to which an active phase of offence can be divided into three categories: I - the pace of mutual activities < 1.5 s per one shared activity, II - the pace of mutual activities from 1.5 to 2.0 s per one shared activity, III - the pace of mutual activities > 2.0 s per one shared activity. The analysis of content activity of leading handball players allowed defining that I and II category can be included to a set of effective categories, and the correlation indicator equalled r = 0.865 (category I), r = 0.623 (category II), and the activities above 2.0 s are ineffective (r = 0.214). The analysis of offensive activities' effect upon the defence efficiency level allowed determining that together with the increase of the pace of mutual activities of offenders, the defence efficiency decreases visibly. It is especially well seen at the long "chains" of mutual, dynamic offenders' activities. This give a high correlation indicator r = 0.854. The above implications unambiguously indicate the necessity to introduce some radical changes in the training process of handball players. The examination of the character of training and match indicates the lack of content relations, which can imply routine attitude towards training without a deep demand analysis. For the need of training knowledge of locomotion character of handball is necessary. Defining a distance which a player covers during a game, and then indicating characteristic running intervals and the speed of covering typical running distances in a game is needed. Examining the distances players cover during a game and training proves earlier assumption that training does not at any rate influence positively the optimal players' preparation for a match. Comparing the distances covered during training and during a game indicates that running distances covered by a player during a match differ substantially from those covered during training. The diagnosis and evaluation of very complex tactic problems is troublesome from the point of view of training process. It should be emphasised that the condition of increasing the tactic level is an objective evaluation of a game, which can be reduced to observing recorded matches, time measurements and tests and trials during training or game. To conclude, the observation of changes occurring in sports sciences and also in the directions of their development, allows determining, to a high probability level, that one of the most essential problem in contemporary sport is constant development of the whole training system. The hitherto conducted analyses indicate that within the confines of the whole system we can separate the following substantial factors: 1) handball development forecasting, 2) determining training, competition and renewal character, 3) determining the criteria of candidate selection and the rules of selection for handball, 4) determining indicators of general and specialised physical preparation in handball, 5) indicating training rules and further education of coaches, 6) determining the role of IHF and EHF in organisational development of handball in the world. Each of these factors is so complex, that it constitutes a complicated system itself. During training process there occur relations between these systems and their optimisation is essential for the efficiency of the training itself. The presented view of sports training system can be considered a specific concept of this system's structure, which presents the most essential elements and relations occurring between them.